L’émigration forcée des enfants britanniques au XIXe siècle - Tri Tran (Cahiers Victoriens et Edouardiens)
Parliamentary Papers, government records and Poor Law Unions’ archives are invaluable sources of information on the condition of pauper emigrants. In the 19th century thousands of young children, including juvenile delinquents, orphans and deserted children, were sent to British colonies by Poor Law Unions and philanthropic societies. This contribution attempts to explain the organization of this emigration and the living and working conditions of these young emigrants in a number of settlements in Canada, Australia and New Zealand.